Find general solution: \(y dx+(x-y^2)dy=0\)
y dx+(x-y2)dy = 0
⇒ydx = (y2-x)dy
\(\implies\)\(\frac {dx}{dy}\) = y2-\(\frac xy\) = y-\(\frac xy\)
\(\implies\)\(\frac {dx}{dy}\)+\(\frac xy\) = y
This is a linear differential equation of the form:
\(\frac {dy}{dx}\)+px = Q (where p=\(\frac 1y\) and Q=y)
Now, I.F = e∫pdy = \(e^{∫\frac 1y dy}\) = elog y = y
The general solution of the given differential equation is given by the relation,
x(I.F.) = ∫(Q×I.F.)dy + C
\(\implies\)xy = ∫(y.y)dy + C
\(\implies\)xy = ∫y2dy + C
\(\implies\)xy = \(\frac {y^3}{3}\) + C
\(\implies\)x = \(\frac {y^2}{3}\) + \(\frac Cy\)
What is the Planning Process?
A relation between involved variables, which satisfy the given differential equation is called its solution. The solution which contains as many arbitrary constants as the order of the differential equation is called the general solution and the solution free from arbitrary constants is called particular solution.
Read More: Formation of a Differential Equation